The pest sap beetle Carpophilus (Myothorax) truncatus Murray, 1864 (Coleoptera: Nitidulidae)—a new synonymy and a related new species of Carpophilus - Semeraro, Linda; Blacket, Mark J.; Rako, Lea; Cunningham, John Paul (Zootaxa, 2023)
Carpophilus truncatus Murray 1864, is a species of sap beetle which has been recorded from many countries worldwide, and has become recognised as an important pest of nuts. In this study, we present a re-description of C. truncatus including diagnostic photographic images of the adults and larvae, and demonstrate that Carpophilus jarijari Powell & Hamilton, 2019 is a junior subjective synonym of C. truncatus. Information about the species’ distribution in Australia is updated. DNA barcode sequence data for C. truncatus is reviewed and augmented to enable differentiation from other morphologically similar Carpophilus species that are associated with nuts as hosts, including the cosmopolitan Carpophilus dimidiatus (Fabricius, 1792), for which C. truncatus has sometimes been misidentified. This analysis revealed that existing reference DNA sequences of “C. dimidiatus” consist of three highly genetically divergent lineages, representing three species: the cosmopolitan C. dimidiatus, the widespread C. truncatus, and a newly described species, Carpophilus imitatus sp. nov., known from south-eastern Asia and Australia.